The Adolescents Overview with Healthy Sexual Behavior in the Risky Environment - Sitti Nur Djannah (International Journal of Evaluation and Research in Education (IJERE), 2017)
Teens today have experienced a shift in morality, thought and behavior patterns because they are influenced by foreign cultures. This is due to lack of progress, especially in the field of transport and telecommunications that are spreading globally at youth culture. Negative attitudes towards adolescent health, such as sexual activity also tend to increase. Turonggo Wiro Budoyo (TWB) Wirobrajan Yogyakarta youth association which is a group of teenagers in the field of traditional dance, jathilan, is identified as a group of young adults at risk of premarital sex. They almost have a close friend (dating) and have intercourse, which is interesting to explore. There are five teenagers who can maintain a healthy sexual behavior. The purpose of research is to know the description of personal factors and external factors that influence adolescents to be able to retain healthy sexual behavior in a risky environment in TWB Yogyakarta youth association. Based on in-depth interviews with five teenagers who declares themselves not dating and a group leader community of TWB, it was shown that an overview that affects teens still behave in a healthy sex despite being in a risky environment is an overview of personal where young people have the ability to hold back emotions, ideals and religiosity attitudes, while the picture of the external consists of a family function where parents do remind norms and religion as well as the ability of adolescents to maintain away from the influence of friends to behave deviate.